Loss of the N-terminal domain of chlorophyllide a oxygenase induces photodamage during greening of Arabidopsis seedlings - Tanaka Ryouichi; Yamasato Akihiro; Tanaka Ayumi (BMC Plant Biology, 2008)
Abstract Background Chlorophyll b is a major photosynthetic pigment in green plants that is synthesized by chlorophyllide a oxygenase (CAO). The regulation of chlorophyll b biosynthesis is an important determinant for the antenna size of photosystems. Chlorophyll b synthesis is partly regulated on a transcriptional level by the expression of the CAO gene. In addition, the synthesis of chlorophyll b is strictly regulated on a protein level by the stability of the CAO enzyme. CAO consists of three domains, which are sequentially named from the N terminus as the A, B and C domains. The A domain of CAO participates in the regulation of the CAO protein stability. Results In order to clarify the physiological function of the A domain, we constructed transgenic Arabidopsis (Arabidopsis thaliana) plants which either overexpressed the complete CAO or a truncated version of CAO lacking the A domain. The transgenic plants overexpressing the A-domain-deleted CAO accumulated an excess amount of chlorophyll b during greening. The transgenic plants which lacked the A domain either died or were obviously retarded when they were exposed to continuous light immediately after etiolation. In addition, the loss of the A domain in CAO impaired another step of chlorophyll biosynthesis, namely the conversion of divinyl-protochlorophyllide a to monovinyl protochlorophyllide a under dark conditions. Conclusion The A domain of CAO regulates the level of CAO, and thus prevents the excess accumulation of chlorophyll b. This function of the A domain is especially important during the greening stage of etiolated seedlings. At this stage, the plants are vulnerable to photodamages which could be caused by excessive chlorophyll b accumulation. In addition, de-regulation of the CAO level affects monovinyl-protochlorophyllide biosynthesis in darkness by unknown mechanisms. In conclusion, the A domain of CAO is essential in the control of chlorophyll biosynthesis and in the survival of seedlings during de-etiolation especially under strong illumination.